Evidence for discrete stages of human natural killer cell differentiation in vivo - Freud, Aharon G. (The Rockefeller University Press, 2006)
Human natural killer (NK) cells originate from CD34(+) hematopoietic progenitor cells, but the discrete stages of NK cell differentiation in vivo have not been elucidated. We identify and functionally characterize, from human lymph nodes and tonsils, four NK cell developmental intermediates spanning the continuum of differentiation from a CD34(+) NK cell progenitor to a functionally mature NK cell. Analyses of each intermediate stage for CD34, CD117, and CD94 cell surface expression, lineage differentiation potentials, capacity for cytokine production and natural cytotoxicity, and ETS-1, GATA-3, and T-BET expression provide evidence for a new model of human NK cell differentiation in secondary lymphoid tissues.